Optimizing and Enhancing Piezoelectric Energy Harvesting Devices - Amri Chaymae; Gaouzi Khawla; Jilbab Abdelilah; el Yousfi Alaoui My Hachem; Azrar Lahcen (E3S Web of Conferences)
This paper presents a study on energy harvesting from very low excitation frequencies 0.7 Hz, 0.9 Hz, and 1 Hz simulating a pedestrian’s walking motion using a piezoelectric energy generator. This generator is based on a cantilever beam model with a concentrated mass at its end. A more complex model was considered, incorporating a test mass of 1 g after various manual mass adjustments. Upon validation through modelling and simulation, the energy harvesting system produced power recoveries of 68 mW, 98 mW, and 196 mW for frequencies of 1 Hz, 0.9 Hz, and 0.7 Hz, respectively. The system was further optimized electrically using the Synchronized Switch Harvesting on Inductor (SSHI) method, which inverts the piezoelectric voltage, increasing the amplitude of the crenels and enhancing the device’s efficiency. This optimization resulted in harvested power increases to 139 mW, 190.3 mW, and 396 mW at the respective frequencies. Overall, power recovery improved by 50% following the electrical optimization. These results demonstrate the potential to enhance and scale up the system for harvesting and storing energy in batteries through a larger-scale prototype. This technology provides a renewable and unlimited energy source, particularly useful for biomedical sensors with strict energy requirements.